From the curricular to the investigative, a look at COVID-19 - Sandra Williams Serrano; Luis Alberto Mass Sosa; Milagros León Regal; José Aurelio Díaz Quiñones (Medisur)
The disease caused by the coronavirus (SARS-CoV-2), which causes COVID-19, has generated a movement towards a review of the entire approach of medical sciences and to delve into all the mechanisms inherent to the immune response associated with this disease. The necessary clinical epidemiological thinking declared in the study plan of the Medicine career is evidenced; research training from the early years. The subject Blood-Immune System includes in its content a large number of health problems due to imbalance in the immune response, which constitutes a clear justification for resizing the scientific training process. The objective of this work is to assess the significance of the subject for the interpretation of the deviations of the immune response and to make suggestions to enhance the research work in it.